POLITICS OF SELECTIVE RECOGNITION: THE PARADOX OF ANIOMA’S IGBO IDENTITY IN STATE CREATION AND NATIONAL POLITICS IN NIGERIA - UROM Charles Egwu; WOSU Moses Victor (PT. Antis International Publisher, 2026)
Objective: This study looks at politics of selective acceptance in Nigeria and the Igbo identity of the Anioma people of Delta state. Anioma people have a linguistic, cultural, historical and social affinity with the Igbo homeland but this identity is not always acknowledged in the national political discourse. In the debates about the creation of states, Igbo identity is sometimes highlighted as a basis for the demand for an Anioma State, while in other socio-political and regional relations within the Niger Delta, it is ignored. This seeming dichotomy throws up pertinent issues of inclusiveness, intergroup relations and national integration in Nigeria at the federal level. Method: The study adopted descriptive qualitative approach and secondary data sources such as government reports, historical records, academic literature and media publications were used in conducting the study. Content analysis was employed to examine the patterns, frequency and dynamics of identity mobilization and marginalisation in data. The framework of the Politics of Recognition is used to provide a basis for the analysis of how conditional acknowledgment affects political representation, resource availability and social legitimacy. Results: The results indicated that the Ogbonje showed a tendency to play up the Igbo identity only when it was politically advantageous, such as in the context of state creation advocacy, and downplay it when it was more advantageous to regional affiliation in the politics of Niger Delta resources. It is a structural anomaly in the Nigerian federal system that is threatening trust, political participation, and intergroup cooperation. The study found that ethnicity is both a political resource and a constraint in the governance process in Nigeria. Novelty: It suggests institutionalized mechanisms for inclusive recognition, representation and coherent identity accommodation policies for promoting national integration in multiethnic federations.